2019
DOI: 10.1371/journal.pone.0225856
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isotemporal substitution of sedentary behavior with light-intensity or moderate-to-vigorous physical activity on cardiometabolic markers in male adolescents

Abstract: Increasing prevalence of sedentary behavior (SB) combined with low levels of physical activity (PA) in children and adolescents has become a growing public health concern. Therefore, this study aimed to identify the daily behavioral pattern of adolescents and examine the isotemporal substitution effects of SB with light-intensity PA (LIPA) or moderate-to-vigorous PA (MVPA) on cardiometabolic markers. In this cross-sectional study, the daily behavioral pattern of Brazilian male adolescents was objectively measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 40 publications
(78 reference statements)
1
24
0
2
Order By: Relevance
“…In the Moura et al study [45], replacing 5-60 min SED with LPA showed positive effects on SBP. However, this result was not significant for any bouts of MVPA.…”
Section: Blood Pressurementioning
confidence: 86%
See 2 more Smart Citations
“…In the Moura et al study [45], replacing 5-60 min SED with LPA showed positive effects on SBP. However, this result was not significant for any bouts of MVPA.…”
Section: Blood Pressurementioning
confidence: 86%
“…Recent research has strengthened the evidence for the association between ISM and metabolic health, as seen in eight cross-sectional studies included in Table 1. Among these studies, seven examined obesity indicators [36,37,39,42,[44][45][46], three studied BP [39,44,45], and five examined blood lipid indicators and glucose-related indicators [39,[44][45][46]52].…”
Section: Effects Of Replacing Sedentary Time With Physical Activity O...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, replacing 30 min of MVPA with sedentary behavior or other types of activities was associated with a 14–17% elevation of cardiometabolic risk. Several previous studies on accelerometer-derived sedentary behavior and physical activity have described the potential effects of replacing sedentary behavior with an equal amount of light intensity activity or lifestyle activity (in other words, breaking sitting time or increasing standing time) to improve health [ 35 , 36 , 37 , 38 , 39 ]. Indeed, many epidemiological studies suggest that reduction in sedentary behavior may have a beneficial effect on health promotion independent of time spent on MVPA [ 12 , 15 , 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…One accelerometer-based study reported that replacing sedentary behavior with physical activity was associated with cardiometabolic health in older adults [ 37 ]. Another study noted the effects of isotemporal substitution of sedentary behavior with light intensity or MVPA on cardiometabolic markers in male adolescents [ 38 ]. Moreover, most of these studies have described a consistent relationship that replacing MVPA with sedentary behavior or light intensity activity could have a harmful effect on cardiometabolic health.…”
Section: Discussionmentioning
confidence: 99%